1998
DOI: 10.1210/endo.139.5.6009
|View full text |Cite
|
Sign up to set email alerts
|

The Growth Hormone (GH) Gene Is Expressed in the Lateral Hypothalamus: Enhancement by GH-Releasing Hormone and Repression by Restraint Stress

Abstract: Recent studies suggest that GH may modulate emotion, behavior, or stress response by its direct actions on the brain, and possible expression of the GH gene in the brain has been predicted. In this study we have investigated whether and where the GH gene is expressed in the brain and how it is regulated. Ribonuclease protection assay and 5'-rapid amplification of complementary DNA ends-PCR analyses indicated that the GH gene was expressed in rat brain, initiating at the identical transcription start point as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…hCS-A expression was detectable at trace levels in brain, testis, ovary, and kidney. Recent studies have reported low levels of GH gene expression in the rat brain (38) and GH and CS gene expression in human testis (39) and ovary (40). These observations suggest that the low level "ectopic" expression from the hGH/P1 transgene that we have observed may instead reflect normal physiologic patterns of low level gene expression.…”
Section: Discussionmentioning
confidence: 43%
“…hCS-A expression was detectable at trace levels in brain, testis, ovary, and kidney. Recent studies have reported low levels of GH gene expression in the rat brain (38) and GH and CS gene expression in human testis (39) and ovary (40). These observations suggest that the low level "ectopic" expression from the hGH/P1 transgene that we have observed may instead reflect normal physiologic patterns of low level gene expression.…”
Section: Discussionmentioning
confidence: 43%
“…IGF-IA, IB and -actin mRNA expressions were detected by reverse transcription-polymerase chain reaction (RT-PCR)/Southern blot hybridization as described previously [9]. The primer pairs used for PCR of IGF-I cDNA can detect IGF-IA and IB at the same time and as different length of fragments (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Species GH GH mRNA Neural Tissues brain human Kyle et al 1981rat Pacold et al 1978Lechan et al 1981Hojvat et al 1982a, b Gossard et al 1987Martinoli et al 1991Yoshizato et al 1998chicken Render et al 1995bRender et al 1995bfrog Yon et al 1991 Lechan et al 1981 Reproductive tissues testis human Untergasser et al 1997, 1998aUntergasser et al 1996, 1998achicken Hull et al 1999 Mol et al 1995bMol et al 1995bdog Eigenmenn et al 1983Mol et al 1995a, 1996Van Garderen et al 1997Selman et al 1991, 1994a, b Mol et al 1995acat Watson et al 1987Mol et al 1995a Lymphoid tissues thymus human Wu et al 1996Sabharwal and Varma 1996Wu et al 1996 rat Binder et al 1994thymic epithelia human Maggiano et al 1994de Mello-Coelho et al 1998Maggiano et al 1994;Wu et al 1996 Varma et al 1993Malarkey et al 1996rat Weigent et al 1988Baxter et al 1991aWeigent et al 1992 human Kao et al 1992b…”
Section: Tissuementioning
confidence: 99%
“…The release of GH from amygdaloid, hippocampal, and hypothalamic cells in vitro is, however, suppressed by SRIF, as is the release of pituitary GH (Pacold et al 1978;Hojvat et al 1982b). However, while restraint stress represses GH gene expression in the rat lateral hypothalamus, it has no effect on pituitary GH mRNA (Yoshizato et al 1998). The turnover of GH mRNA in the rat hypothalamus also appears to be more rapid than in pituitary tissue (Yoshizato et al 1998), and the increase in hypothalamic GH mRNA induced by GHRH is far greater than the GHRH-induced increase in pituitary GH mRNA (Yoshizato et al 1998).…”
Section: Extrapituitary Gh: Tissue-specific Synthesismentioning
confidence: 99%